Some words about the adaptation of borrowed German words from the field of science in the Polish language - Sikorska-Bujnowicz, Katarzyna (Acta Universitatis Lodziensis. Folia Germanica, 2014)
The matter under consideration in this article is the problem of borrowed German lexical elements and their life in the borrowing Polish language. The starting point is a short overview of the elements of the lexical field of science and their change of meaning in the Polish language.